MULTILITERACY LEARNING MODEL THROUGH SYNERGY BETWEEN THE NEEDS OF THE WORKPLACE AND LEARNING LANGUAGE SKILLS COURSES - Heny Friantary; Ixsir Eliya (Universitas Negeri Makassar, 2023)
The research objective of this research is to develop a multiliteracy learning model for the course of Keterampilan Berbahasa. The research procedure applied the development model by Borg and Gall, which consisted of the following stages: needs analysis, product design, product development, validity test, product revision, small field test, and evaluation. The research subjects were divided into three categories: need analysis participants, expert participants, and user participants. Data were collected through observation, questionnaires, and interviews. The data analysis employed qualitative analysis and descriptive statistics methods. Based on the need analysis of the students and lecturers, can be implied that the multiliteracy learning model needs to be developed to be implemented on the course of Keterampilan Berbahasa by building a synergy between the needs of the workplace and the learning system. The learning model development product consists of 3 parts, namely introduction, content, and closing. Based on the results of the validation test by the content expert has very decent qualification with a percentage value of 84%. The result of the validity test by media expert has a decent qualification with a percentage value of 80%. Language validity has a decent qualification with a score percentage of 76%. The validity tests above show that the product can go on the next process, namely testing on students. The product designed in this development study is supported by systematic and appropriate syntax, making the product feasible for use in the course of Keterampilan Berbahasa at a tertiary level in effective and efficient ways.